The Piaget’s learning theory and its implications for educational practice - Dongo M., Adrian (2008)
Our aim is to show the constitution of a theory of the learning in Jean Piaget’s work from the overcoming of the secular opposition between learning and intelligence and on essa base to discuss the pedagogic traditional practice and his possible transformations. For it, we will effect the following analyses: 1) analysis of the relations that exist between theory and pedagogic practice, 2) analysis of the historical impases between the theories of the learning and the theories of the intelligence, 3) analysis of the solution given by Piaget to this impase and the construction of a new theory of the learning, 4) discussion of the pedagogic traditional practice and his possible transformations taking a new theory of the learning as a base.